Mantle Melting Conditions of Mare Lavas on South Pole–Aitken Basin of Lunar Farside - Yishen Zhang; Rajdeep Dasgupta; Dian Ji; Cin‐Ty Lee; Ye Peng; Bernard Charlier; Ziliang Jin; Jian Chen; Olivier Namur (Geophysical Research Letters)
Abstract The understanding of thermal evolution and magmatic history of the Moon has so far been informed by studies of rock samples from the nearside. However, the recently completed Chang'E‐6 mission by China National Space Administration has returned the first samples from the lunar farside, providing a unique opportunity to refine our understanding of the Moon's history. To provide context for future research on these returned samples, we use remote sensing data and geochemical modeling to infer temperature and pressure conditions of the lunar mantle that could generate the surface lavas in Apollo basin on the lunar farside. The estimated melt‐mantle equilibration conditions cover a temperature range from 1,170°C to 1,430°C and a pressure range from 0.3 to 1.7 GPa, requiring mantle potential temperatures of 1,220°C–1430°C. The mantle melting conditions on farside are cooler and shallower than those on the nearside mantle, if the mantle compositions are similar.